Physicochemical, textural and microbiological properties of optimised wheat bread formulations as affected by differently fermented sourdough - Hayta, Mehmet; Ertop, M. Hendek (Codon Publications, 2019)
The aim of the study was to evaluate the physicochemical properties, microbiological and textural features of optimised wheat bread formulations consisting of sourdough (A) prepared with two differ...
Keywords: 2. Zero hunger